Pengaruh Harga Batubara Acuan (HBA) dan Debt to Equity Ratio (DER) Terhadap Harga Saham Perusahaan Energi Subsektor Batubara Yang Terdaftar di BEI Periode 2020-2024 - Andri Fabian Mahardika; Dedi Mulyadi; Santi Pertiwi Hari Sandi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the conditions of the Benchmark Coal Price (HBA), Debt to Equity Ratio (DER), and stock prices, as well as to examine the correlation and influence of HBA and DER on stock prices, both partially and simultaneously, in coal subsector companies listed on the Indonesia Stock Exchange for the 2020-2024 period. This study uses a quantitative approach with descriptive and verification analysis methods and path analysis techniques. Secondary data were obtained from the Indonesia Stock Exchange, the Ministry of Energy and Mineral Resources, and company financial reports. The research sample consisted of 5 coal subsector companies selected using a purposive sampling technique, with a total of 100 quarterly observation data. Data processing was carried out using SPSS 26 software. The results showed that there was no correlation between HBA and DER. Partially, HBA had a positive and significant effect on stock prices, while DER had a negative and significant effect on stock prices. Simultaneously, HBA and DER had a significant effect on stock prices, indicating that stock prices were influenced by commodity price dynamics and company capital structure.